Effects of clay materials and moisture levels on habitat preference and survivorship of Formosan subterranean termite, Coptotermes formosanus Shiraki (Blattodea: Rhinotermitidae) - Jin,Zhengya; Chen,Jian; Wen,Xiujun; Wang,Cai (PeerJ, 2020)
Formosan subterranean termites, Coptotermes formosanus Shiraki, usually transport clay materials into tree hollows and bait stations. Our previous research showed that C. formosanus preferred to aggregate in the locations containing field-collected clay samples, but it was not clear whether this preference was influenced by clay types and/or moisture. In the present study, we conducted multiple-choice tests under low-moisture (25% moisture) or moderate-moisture (50% moisture) conditions to evaluate the aggregation and wood-feeding preferences of C. formosanus responding to hollow wooden cylinders (simulation of tree hollows) or baiting containers (simulation of bait stations) filled with different clay materials (bentonite , kaolin, chlorite, illite, or attapulgite), soil, or unfilled. Under low-moisture conditions, the majority of termites were found in the wooden cylinders or baiting containers filled with bentonite. Under moderate-moisture conditions, however, termites preferred to aggregate in wooden cylinders filled with chlorite or attapulgite; the percentages of termites that stayed in baiting containers filled with chlorite, attapulgite or soil were similar, which were significantly higher than those that filled with kaolin, illite, or unfilled. We then conducted no-choice tests to study the effect of clay materials on termites. Under low-moisture conditions, clay filled in the baiting containers significantly increased survivorship and body water percentage (an indicator of termite vigor) of termites, whereas no similar effect was detected under moderate-moisture conditions. This study demonstrated that both clay type and moisture affect termites’ preference.
Keywords: Soil organism; Clay-insect interaction; Bentonite; Chlorite; Attapulgite